Psychological impact of the state of emergency over COVID-19 for non-permanent workers: a Nationwide follow-up study in Japan - Saito, Shota; Tran, Huyen Thi Thanh; Qi, Ruan; Suzuki, Kenji; Takiguchi, Toru; Ishigami, Kazuo; Noto, Shinichi; Ohde, Sachiko; Takahashi, Osamu (BMC public health, 2021)
Background The outbreak of COVID-19 has caused mental health problems and increased unemployment due to the economic recession. This survey aimed to assess the psychological impact of the state of emergency. We estimated changes in mental health, quality of life, and unemployment experience for general workers during the first COVID-19 outbreak in Japan. Methods We conducted a nationwide follow-up study. During the periods of March 26 to April 6, 2020 and June 26 to July 2, 2020, we used the internet to survey general workers aged 15 to 59 years in Japan. The questionnaire items covered employment status and socioeconomic factors, and we used the Center for Epidemiologic Studies Depression Scale (CES-D) and EQ-5D-5L to assess depression and health-related quality of life (HR-QOL), respectively. The differences in outcomes of permanent and non-permanent workers were analyzed using propensity score analysis. A multiple linear regression analysis was performed to examine the relationship between unemployment and CES-D scores. Results We included 2351 subjects in the analysis. Changes in both CES-D scores and utility were not significantly different between the two groups. However, a significant difference was found regarding the rate of unemployment, which was associated with higher CES-D scores. Conclusions The present study demonstrated that the mental health of non-permanent workers was not negatively affected following the state of emergency due to COVID-19 in Japan. Unemployment is an important factor that influences the mental health of general workers.